O caso Althusser: articulações possíveis entre Psicanálise e Direito Penal - Lopes, Leonardo (2015)
This research weaves articulation possibilities between the psychoanalytic field and the criminal law, using the case of the philosopher Louis Althusser, while a paradigm of tragic dimension of the not imputable. There for, it is used as an methodology the analyze of his autobiographical memories, written on "The Future Lasts Forever" (1990), five years after strangled his wife and get declared irresponsible because of a melancholic psychosis. The place of the psychotic in legal discourse calls psychoanalytic knowledge for the discussion of responsibility, which is present in the work of Jacques Lacan, since the beginning of his teaching, when he looked for an dissociation between the term "mental offender" from psychiatry, such as specific clinical operators, as" passage to the act" as well. In addition, terms common to psychoanalysis and the criminal speech, such as law, crime and guilt, assume different meanings in each field, a scenario that leads research in two means. First, the psychosis approach, as language structure produced by foreclosure of the significant in the Name-of-Father, and Althusser´s melancholy, as a permanent mourning from the emptiness left by Verwerfung. Second, the conception of homicidal crime as a passage to the act and therefore act caused by guilt feeling and whose inevitable consequence accountability. We conclude, therefore, that there is a hiatus between the law subject from the of subject of the unconscious, among legal responsibility and individual responsibility, but that does not prevent its dialogue. The subject is always responsible for his position in the structure, and the incidence of the law by criminal summons may open the possibility for stabilization. In this sense, the crime committed by Althusser was not a motivated act, but a solution against suicide law, which reveals the very melancholy unconscious structure, and that by no means could have stopped him from answering legally